Humanização da assistência e das condições de trabalho: a visão dos enfermeiros de um hospital universitário - Sousa, Delvane José de (2010)
With the objective of introducing humanized practices in the health environments, in 2002 the Ministry of Health launched the National Humanization Policy (PNH), which aims at reorganizing the health work processes proposing social relation changes that involve workers and managers in the organization and conduct of services. The aim of this research was to estimate the satisfaction reported by the nurses in a university hospital concerning to the humanization of the hospital work, according to the guidelines of PNH. Data were collected through a questionnaire structured in four parts: sociodemographic data, nurses' information level about PNH, Likert scale and suggestions. 78 questionnaires were distributed among the nurses, of which 71 returned to the researcher. Data received statistical treatment through the descriptive techniques, factorial analysis and suggestions. From the respondents, 82% of the nurses were female and 75% were in the age group of 20 to 29 years old. When rotating variables the following factor cathegories appeared in order of variance: (1) right to participation, management support, flexibility in conducting work, permanent communication and education; (2) environmental signaling, identification of the professionals, privacy respect, users' communication and orientation; (3) professional formation, services offered to the population and the material available for work; (4) satisfaction related to the professional achievement, reward received and general work conditions; (5) Environmental conditions of work (hygiene and safety); (6) management model and equipments available; (7) agility in attendance and service confidence; (8) number and turnover of the professionals. This study made easy the understanding of the professional perceptions about the humanization of the work conditions in the hospital environment, then enabling a reflexion. Knowledge of this reality can contribute with suggestions for the innovation in the management, concerning the real necessities of the nurses, enabling the professional with a fundamental place related to the humanized care in hospital environment.